Blockchain technology for social impact: opportunities and challenges ahead. Issue 3 (2nd September 2017) - Al-Saqaf, Walid; Seidler, Nicolas
ABSTRACT: While much has already been written about blockchain applications and prospects in the FinTech industry, little research has been done to explore blockchain technology's user-centric paradigm in enabling various applications beyond banking. This article is an effort to contribute to that body of scholarship by exploring blockchain technology's potential applications, and their limits, in areas that intersect with social impact, including human rights. This article explores whether blockchain technology and its core operational principles – such as decentralisation, transparency, equality and accountability – could play a role in limiting undue online surveillance, censorship and human rights abuses that are facilitated by the increasing reliance on a few entities that control access to information online. By doing so, this article aims at initiating a scholarly curiosity to understand what is possible and what is to be concerned about when it comes to the potential impact of blockchain technology on society.